Kontekstualisasi Cerai Talak dalam Fikih dan Hukum Nasional di Indonesia - Fikri Fikri; Saidah Saidah; Aris Aris; Wahidin Wahidin (Al-Ulum, 2019)
This paper aims to respond contextualization of divorce through in fiqh and national law in Indonesia. This study is conducted with a qualitative descriptive using normative theological, sociological, and formal juridical approaches. The study shows that;1) divorce is absolute right of a husband to his wife so that it is legitimate, the belief is actualized that divorce is spoken by husband is a legitimate fiqh perspective, because the law automatically applies who said it; 2) Divorce is done outside the Religious Court there is no legal force, wife cannot claim her rights, Islamic society must obey the legal system in Indonesia although talak is sourced from fiqh can apply automatically, but islamic society cannot ignore in law enforcement from the legal system that applies in Indonesia.